Correlation of Femoral Cartilage Thickness and Osteoporosis in Female Patients with Knee Osteoarthritis - Gamze Altuğ Özövez; Alev Alp (Türk Osteoporoz Dergisi)

(untitled)
Objective:To evaluate the relationship between ultrasonographic femoral cartilage thickness and presence of concomitant osteoporosis in a group of female patients with knee osteoarthritis (OA).Materials and Methods:This study included 118 women with knee OA who visited our outpatient clinic. Demographic data were collected, radiologic grading using Kellgren Lawrence (K-L) scale, ultrasonographic femoral cartilage thickness (FCT) evaluation, pain intensity evaluation, disability evaluation using OA index [Western Ontario and McMaster Universities Osteoarthritis index (WOMAC)], quality of life measurement using Short Form-36 (SF-36) and bone density measurement using dual-energy X-ray absorptiometry (DXA) were conducted for each patient.Results:We found that 58 patients (median age: 64.5 years, range: 50-75) had osteoporosis (group 1) and 60 patients (median age: 62 years, range: 51-75) did not have osteporosis (group 2). Group 2 had higher body mass index (BMI) in addition to lower WOMAC, SF-36 physical function, physical role limitation, pain and social function scores. The severity of osteoporosis and K-L staging were negatively correlated. The DXA femoral neck and total lumbar T-scores were higher in the advanced stages of OA. FCT had no significant correlation with age, WOMAC index and SF-36 scores. Moreover, the left knee FCT was negatively correlated with BMI.Conclusion:Radiologic staging of OA had a negative correlation with osteoporosis but no significant correlation with the quantitative measurement of FCT using ultrasonography.